Exploring approaches for teacher representatives on school governing bodies to cope with demanding relationships - Slabbert, Lajane (University of the Free State, 2021)
The challenges School Governing Body (SGB) teachers experienced were shown in the study and additional influential factors affecting the best interest of primary schools. This study was grounded in a theoretical framework focusing on approaches to coping with demanding relationships in the SGB as teacher representatives. The theoretical framework was embedded in the choice Theory of William Glasser and the theoretical perspective of representative democracy. This study comprised a qualitative research method applied in five primary schools in the Motheo District, Bloemfontein, Free State, South Africa. Data were collected using interviews with five principals, nine SGB teachers, and seven SGB parents, and open- ended questionnaires were conducted with eight teachers. Furthermore, non- participant- observation was done in each school as well. Four themes emerged from the qualitative research, and the primary focus was on the role of the teacher in improving relationships in the SGB. Findings revealed that to put the schools' needs first and improve functionality in the SGB, teachers need to gain a greater understanding of the SGB, not be afraid to voice concerns, and focus on building stronger working relationships with colleagues in the SGB.
Dissertation (M.Ed. (School of Education Studies))--University of the Free State, 2021
Keywords: School governing body (SGB); Teachers’ representative; Parents; Relationships management; Conflict; Emotional intelligence (EI); Relationships